Determination of Novel Estimations for the Slater Difference and Applications - Muhammad Adil Khan; Hidayat Ullah; Tareq Saeed; Zaid M. M. M. Sayed; Salha Alshaikey; Emad E. Mahmoud (Complexity)
The field of mathematical inequalities has exerted a profound influence across a multitude of scientific disciplines, making it a captivating and expansive domain ripe for research investigation. This article offers estimations for the Slater difference through the application of the concept of convexity. We present a diverse type of applications that stem from the main findings related to power means, Zipf–Mandelbrot entropy, and within the field of information theory. Our main tools for deriving estimates for the Slater difference involve the triangular inequality, the definition of the convex function, and the well-established Jensen inequality.